Abdominal Massage as Nursing Implementation of Feeding Intolerance of Preterm Infants in Neonatal Intensive Care Unit: A Systematic Review - Darmareja, Rycco; Jansen, Susiana (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
The immaturity of the gastrointestinal tract of preterm infants can increase the prevalence of feeding intolerance that must be addressed by nurses. Massage is considered effective and is often used in neonatal intensive care. This study aims to identify the effectiveness of complementary therapy in the form of abdominal massage as a nursing implementation strategy for premature infants with feeding intolerance in the NICU. The study method refers to the PRISMA 2020 checklist with the following keywords: "Feeding Intolerance" AND "Newborn" OR "Premature" AND "Abdominal massage" AND "Neonatal Intensive Care Unit" AND "Nursing". Article searches were conducted on Google Scholar, Springer Link, Scopus, and PubMed databases by applying several criteria including full-text articles relevant to the study objectives, written in Indonesian or English, published in the last 3 years, and using experimental study designs, then continued critical appraisal using the Joanna Briggs Institute (JBI) instrument. Based on the search results, 74 articles were found and after screening only 5 articles were used. The results of the study showed that abdominal massage was considered to have a positive impact on reducing the residual volume of the stomach, vomiting behavior, and abdominal distension. Based on this, it is recommended that abdominal massage can be performed at least twice per day to control feeding intolerance in preterm infants in the neonatal intensive care unit.